Analysis of Variables Affecting Employee’s Turnover Intention Using Structural Equation Modeling (SEM) (Case Study at PT Wonokoyo Jaya Corporindo, Pasuruan) - Yuliasia, Yeni; Santoso, Imam; Hidayat, Arif (Fakultas Teknologi Pertanian Universitas Brawijaya, 2012)
The high turnover rate gives significant losses for the company. These losses are mainly about the costs for training new employees and obtaining the competences as mastered by the leaving workers. PT Wonokoyo Jaya Corporindo is one of the companies in Indonesia which produces various kinds of processed foods ​​from chicken, such as sausages and nuggets. Last year, the employees’ turnover rate is very high so that it leads to disrupted production activities and the decline of corporate performance. The aim of this research was to analyze the variables that affect employees’ turnover intention, such as salary and job satisfaction as well as social support. The samples used in this research were 115 workers of Further and Sausage Processing Plant of PT Wonokoyo Jaya Corporindo. The main instrument was a questionnaire that measured by the Likert scale. The Structural Equation Modeling (SEM) with LISREL 8.7 was deployed to analyze the relationship between those investigated independent and dependent variables. The results show that salary satisfaction, social support and job satisfaction have negative effects on the turnover intention, which are illustrated by t-values of -2.49, -2.09 and -2.34, repectively. In addition, salary satisfaction and social support give positive effect onemployees’ job satisfactions which are figured by t-value of 3.29 and 3.14, respectively. Keywords: salary satisfaction, social support, job satisfaction